Development of vehicle driver fatigue monitoring and prevention system - Thum, Chia Chieh; Mustafa, Mohd. Marzuki; Hussain, Aini (Penerbit Universiti Sains Malaysia, 2004)
Driver fatigue is a serious hazard in transportation systems. It has been identified as a direct or contributing cause of road accident (Gander et al., 1993). Fatigue can seriously slow reaction time, decrease awareness and impair a driver’s judgment. It is concluded that driving while drowsy is similar to driving under the influence of alcohol or drugs (National Sleep Foundation, 2000). In industrialized countries, fatigue has been estimated to be involved in 2% to 23% of all crashes (Knipling & Wang, 1995).